Quercetin Stimulates Insulin Secretion and Reduces the Viability of Rat INS-1 Beta-Cells - Michael Kittl; Marlena Beyreis; Munkhtuya Tumurkhuu; Johannes Fürst; Katharina Helm; Anna Pitschmann; Martin Gaisberger; Sabine Glasl; Markus Ritter; Martin Jakab (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Previously we described insulinotropic effects of Leonurus sibiricus L. plant extracts used for diabetes mellitus treatment in Traditional Mongolian Medicine. The flavonoid quercetin and its glycoside rutin, which exert anti-diabetic properties in vivo by interfering with insulin signaling in peripheral target tissues, are constituents of these extracts. This study was performed to better understand short- and long-term effects of quercetin and rutin on beta-cells. Methods: Cell viability, apoptosis, phospho-protein abundance and insulin release were determined using resazurin, annexin-V binding assays, Western blot and ELISA, respectively. Membrane potentials (Vmem), whole-cell Ca2+ (ICa)- and ATP-sensitive K+ (IKATP) currents were measured by patch clamp. Intracellular Ca2+ (Cai) levels were measured by time-lapse imaging using the ratiometric Ca2+ indicator Fura-2. Results: Rutin, quercetin and the phosphoinositide-3-kinase (PI3K) inhibitor LY294002 caused a dose-dependent reduction in cell viability with IC50 values of ∼75 µM, ∼25 µM and ∼3.5 µM, respectively. Quercetin (50 µM) significantly increased the percentage of Annexin-V+ cells within 48 hrs. The mean cell volume (MCV) of quercetin-treated cells was significantly lower. Within 2 hrs, quercetin significantly decreased basal- and insulin-stimulated Akt(T308) phosphorylation and increased Erk1/2 phosphorylation, without affecting P-Akt(S473) abundance. Basal- and glucose-stimulated insulin release were significantly stimulated by quercetin. Quercetin significantly depolarized Vmem by ∼25 mV which was prevented by the KATP-channel opener diazoxide, but not by the L-type ICa inhibitor nifedipine. Quercetin significantly stimulated ICa and caused a 50% inhibition of IKATP. The effects on Vmem, ICa and IKATP rapidly reached peak values and then gradually diminished to control values within ∼1 minute. With a similar time-response quercetin induced an elevation in Cai which was completely abolished in the absence of Ca2+ in the bath solution. Rutin (50 µM) did not significantly alter the percentage of Annexin-V+ cells, MCV, Akt or Erk1/2 phosphorylation, insulin secretion, or the electrophysiological behavior of INS-1 cells. Conclusion: We conclude that quercetin acutely stimulates insulin release, presumably by transient KATP channel inhibition and ICa stimulation. Long term application of quercetin inhibits cell proliferation and induces apoptosis, most likely by inhibition of PI3K/Akt signaling.